ENHANCING STUDENTS’ LEARNING OUTCOMES IN CLASSICAL CRYPTOGRAPHY THROUGH INTERACTIVE 3D SIMULATIONS - Novayani, Wenda; Alhuda, Iqbal (Politeknik Caltex Riau, 2024)
Cryptography is the study of how to transform data or information into a form that is unreadable by others, thus ensuring the security of the data. Based on a questionnaire conducted among students of Politeknik Caltex Riau (PCR) who have studied classical cryptography, the Vigenere Cipher and Affine Cipher were found to be the most difficult algorithms to understand. This research aims to investigate the improvement in students' knowledge of classical cryptography through interactive 3D simulations. The experiment was conducted on 30 PCR students by comparing two learning groups: a control group (using textbooks) and an experimental group (using 3D simulations). The results showed that the average post-test score for the control group was 67.33 point, while the experimental group achieved an average score of 83.33 point. Thus, learning with 3D simulation media can serve as an effective alternative medium, with a confidence level of 95%, to enhance students' understanding of classical cryptography. Meanwhile, the satisfaction level indicates that 86.75% of students are satisfied with learning through interactive 3D simulation media. This indicates that the use of classical cryptography learning media through 3D simulations provides a significant improvement in student learning outcomes.